Antidandruff Activity of Polyherbal (Murraya koenigii, Moringa oleifera, and Psidium guajava) Extract against Malassezia Species: In Silico Studies. (26th May 2022) - Sharma, Akshata; Sakthiselvan, Punniavan; Karthick, V.; Subraja, R.; Srinivasan, T.; Amudha, K.; John, Shani T
Abstract : Dandruff is one of the leading causes of hair fall and is commonly caused by bacterial and fungal species especially the Malassezia species. The lipolytic enzymes of the Malassezia species play an important role in obtaining lipids from the environment, and they are necessary for the growth and pathogenicity of Malassezia . Therefore, the lipases of the three most commonly ( Malassezia globosa, Malassezia furfur, and Malassezia restricta) affecting Malassezia species have been taken for the In-silico studies. The three-dimensional structure of the lipase of Malassezia globosa (PDB ID: 4ZRE) was retrieved from protein data bank, and the other two proteins of the two species ( Malassezia furfur and Malassezia restricta ) were built using homology modelling by Swiss modeler. The lipases of the Malassezia species along with the 16 bioactive compounds of the polyherbal ( Murraya koenigii, Moringa oleifera, and Psidium guajava ) ethanolic extract predicted by GC-MS analysis were taken for the molecular docking studies. The pharmacokinetic properties of the bioactive compounds were predicted. Thus, the molecular docking results revealed that the bioactive compound flavone with score of −7.160 Kcal/mol, isopropyl stearate with binding score of −10.107 Kcal/mol, and eugenol with a binding score of −8.296 Kcal/mol have shown good binding affinity against the lipase of Malassezia restricta, Malassezia globosa, and Malassezia furfur, respectively. Hence, these compounds can be further investigated by in-vitro and in-vivo studies to be used as potential drug candidates.